New medical technologies influence on the quality of medical care in megalopolises (on the example of Moscow city) - E. I. Aksenova (Здоровье мегаполиса)
Background. The effective development of healthcare and, in particular, clinical medicine, increasingly depends on the unique medical technologies and modern equipment used. Therefore, in order to form a competitive healthcare system in a megapolis, it is important to introduce a management mechanism that allows constant monitoring of emerging new technologies and a comprehensive assessment of their impact on changing the quality of medical care, assessing their contribution to public health, that is, creating a“technological funnel” for the healthcare system. Purpose. The purpose of this study is to identify the urgent problems in the analysis and comprehensive assessment of new medical technologies and determine the possible mechanisms for their introduction into clinical practice. Materials and methods. The methodology of this work is to study the literature and research of the most successful practices of introducing new medical technologies (on the example of the capital’s healthcare), study the opinions of the population and healthcare professionals based on the analysis of social networks. Results. Based on the systematization of information obtained by the authors in the course of the study, authors identified the most important new medicaltechnologies for the population and health care professionals, which, in their opinion, have changed the landscape of the capital’s health care for the better. Authors determined significant criteria for improving the efficiency of the health care system through the search, comprehensive assessment and scaling of innovative practices in clinical medicine. Discussion. The creation of a «technological funnel» in the health care system of the capital makes it possible to conduct comparable research on the quality of medical care provided with many countries of the world. In addition, the constant search and comprehensive assessment of new medical technologies, potentially suitable for implementation in city clinics, can significantly influence theimprovement of the quality of medical care provided to the population. Conclusion. Solving the problems associated with the optimization of search processes, comprehensive assessment, unification of the processes of introducing new medical technologies, can significantly improve the quality of medical care, as well as affect the contribution of health care to the health of citizens. At the same time, such studies require careful research and search for approaches that meet modern realities.